Self-Compassion dalam Bidang Akademik Siswa : Hero or Zero? - Dwi Rizky Fitria (Universitas Pendidikan Indonesia, 2024)
Human life will not be separated from trials and problems, one of which is in the academic field. This academic field is one of the important things for a student because it will support and affect his future. Because of the importance of this academic role, students often feel anxious and worried about everything related to their academic field, which often causes negative behaviour that affects themselves and their environment. Therefore, this study will examine the role of self-compassion in matters relating to the academic field in students. This research was conducted using the Systematic Literature Review (SLR) method. The results of this study show that self-compassion has an important role in helping students respond to negative things that happen in their lives, especially those related to the academic field, so that it becomes a saviour so that students do not respond negatively to things that happen to them and can manage their emotions well and channel them into positive actions.